Welfare aspects in breeding brachycephalic dogs - Gendur, Boglárka Virág; Fazekas, Natasa (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2025)
Aim of our stud was to discover how different traits of brachycephalic dogs are connected to the frequency and number of their symptoms, and what are the consequences of these in making breeding strategies. 42 pugs and 19 French bulldogs were investigated during regular vet checks. We’ve recorded all symptoms connected to brachycephalic syndrome discoverable and registered in their anamnesis, by the help of veterinarians. Next to recording the dogs’ breed, sex, colour the following body measures were taken: length of the nose bridge, height at withers, and length of the topline. The ratio of all disease is much higher in our study than reported in a recent questionnaire study in Hungary, suggesting the need of objective control when trying to measure frequencies instead relying on dog owners. Non-recognized colour variants had shown late onset diseases significantly more frequently, enlightening how puppy mills work. However, eye defects appearing as a consequence of head conformation being more frequent in registered colours point on the effect of breeding determined by dog shows. Nose length being significantly longer in healthy dogs suggests, that this quantitative measure could be used in selection.